Numerical analysis of wavelength conversion based on semiconductor optical amplifier integrated with microring resonator notch filter - Razaghi, M.; Gandomkar, M.; Ahmadi, V.; Das, Narottam; Connelly, M. (na, 2011)
In this paper, we numerically investigate the wavelength conversion using semiconductor optical amplifier (SOA) integrated with microring resonator. In the model all nonlinear effects, which can appear in picosecond and subpicosecond pulse regime, are taken into account. It is shown that with three coupled microring resonators, output four-wave mixing (FWM) signal generated by the SOA can be filtered perfectly. Moreover, it is demonstrated that microring resonator can be used for modifying the output FWM signal shape and spectrum. The output time bandwidth product is also enhanced by this technique. © 2011 IEEE.